1997
DOI: 10.1289/ehp.97105s4865
|View full text |Cite
|
Sign up to set email alerts
|

The causes and prevention of cancer: gaining perspective.

Abstract: 865-873 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…It is known that damage of the genetic material plays a key role in the etiology of cancer [ 5 , 6 , 7 ], therefore, we investigated for the first time the effects of the universal mobile telecommunication system (UMTS) signal on DNA stability in human glioblastoma cell lines (U87, U251 and U373). Additionally, we included further human nerve tissue derived cell lines i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that damage of the genetic material plays a key role in the etiology of cancer [ 5 , 6 , 7 ], therefore, we investigated for the first time the effects of the universal mobile telecommunication system (UMTS) signal on DNA stability in human glioblastoma cell lines (U87, U251 and U373). Additionally, we included further human nerve tissue derived cell lines i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We found in a recent investigation with human-derived cells that some of them cause damage of the genetic material, while other toxic effects (acute cytotoxicity, immunological effects and estrogenic properties) were only moderate or lacking (Koller et al 2013, 2014). Genetic damage is involved in etiology of various diseases, i.e., it plays a key role in the induction of cancer and is also involved in neurodegenerative disorders, atherosclerosis, infertility and aging (Ames and Gold 1997; Ames et al 1993). Therefore, our previous findings indicate that adverse effects, which are related to DNA damage, may be induced in users of these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…1012 During approximately the past decade, the associations between coffee consumption and many diseases, including hypertension, cardiovascular diseases, and cancer, have been studied, and its effects have been found to be harmful to health. 13 , 14 However, several recent prospective cohort studies have indicated that coffee consumption lowers the risks of diabetes mellitus (DM), cardiovascular diseases, and cancer. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%